Personality and Word Use: Study on Czech Language and the Big Five - Kučera, Dalibor; Haviger, Jiří; Havigerová, Jana M (Journal of psycholinguistic research, 2022)
The study is a follow-up to three published anglophone researches examining the relation between the use of linguistic categories and personality characteristics as outlined in the Big Five model, with the purpose of replicating these and elaborating for the Czech language. The comparative research study in Czech focuses on analysis of both grammatical and semantic variables in six types of text (written and oral), produced by N = 200 participants. Within the study, there were six confirmed relations, however, these appear only in certain types of text. The results show not only an essential role of the text register, but they also allow us to evaluate the universality of findings of studies in English in comparison with other, especially Slavic, languages.
Keywords: lingvistika; Language; Česká republika; osobnost; lidé; Linguistics; Personality; Czech Republic; jazyk (prostředek komunikace); sémantika; Semantics; Humans